Farm Productivity In The EU Sustainable Development Concept - Does Farm Size Matter? - Ewa SZAFRANIEC-SILUTA; Agnieszka STRZELECKA; Danuta ZAWADZKA (Communications of International Proceedings, 2021)
The aim of the research is to assess the implementation of the foundations of EU sustainable development with respect to the improvement of productivity of agricultural production factors, especially in relation to very small farms in Poland, against the background of trends in the European Union. The research was based on the statistics of the European FADN (Farm Accountancy Data Network). They concerned farms in the EU, with particular emphasis on entities in Poland, in 2010-2019. The analysis focused on the assessment of land productivity, labor productivity and capital productivity. With reference to the EU sustainable development goals, an increase in the values ​​of the above indicators in the analyzed period was assumed. The research was carried out in two stages. In the first one, the productivity of production factors of an average farm in Poland was compared with an average farm in the European Union. In the next stage, the performance of very small farms was assessed against the background of farms of various economic size classes in Poland against the EU. The productivity of an average farm in Poland is much lower than that of a typical unit in the European Union, both in terms of land, labor and capital. However, in the case of Poland, these measures grew at a slightly faster pace in the period of implementation of the sustainable development goals (2015-2019) than in the case of an average farm in the European Union. Productivity of land, labor and capital varies for farms from different economic size classes. In the case of units in Poland, there is a noticeable tendency that with the growth of the economic class, the average value of the analyzed measures increases. Land and labor productivity in the case of very small farms in Poland increased during the implementation of the sustainable development goals. At the same time, these entities recorded a decline in capital efficiency.
Keywords: farms; labor productivity; capital productivity; land productivity; EU sustainable development; very small farms